La lingua dei Rom e dei Sinti - Agresti, Giovanni; Meli, Giulia (Linguistik Online, 2025)
This article focuses on Romani old settlement varieties of Italy. Emphasising the complexity of the sociological, historical and ideological stratifications of the topic (chapter 1), in chapter 2 the authors present the shared understandings on the early phases of the historical development of the Romani Linguistic Community (RLC) and deal with its first attested appearences on the Italian soil, also pointing at some problems linked to the collection of reliable demographic and demolinguistic estimates; chapter 3 provides an overview of the principal Italian old settlement Romani dialects and proposes a description of these varieties, including some conservative and innovative features of their phonetic and phonological system, along with some morphological, syntactic and lexical characteristics; in chapters 4 and 5 the language policy measures planned by the Italian State for the preservation of linguistic minorities are examined, highlighting the serious difficulties that hinder the Italian RLC from being recognised as such, but finding some recent positive interventions of Regione Calabria and Regione Abruzzo which promote a change of pace on the recognition and fostering of the RLC in Italy.